2014
DOI: 10.1051/0004-6361/201423472
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field topology of the unique chemically peculiar star CU Virginis

Abstract: Context. The late-B, magnetic, chemically peculiar star CU Vir is one of the fastest rotators among the intermediate-mass stars with strong fossil magnetic fields. It shows a prominent rotational modulation of the spectral energy distribution and absorption line profiles due to chemical spots and exhibits a unique, strongly beamed variable radio emission. Aims. Little is known about the magnetic field topology of CU Vir. In this study, we aim to derive detailed maps of the magnetic field distribution over the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(171 citation statements)
references
References 49 publications
9
162
0
Order By: Relevance
“…Our ZDI analysis of GJ65 was carried out with the code described by Kochukhov et al (2014) and Rosén et al (2016).…”
Section: Global Magnetic Field Topologymentioning
confidence: 99%
“…Our ZDI analysis of GJ65 was carried out with the code described by Kochukhov et al (2014) and Rosén et al (2016).…”
Section: Global Magnetic Field Topologymentioning
confidence: 99%
“…The latter is feasible for early-type stars (see e.g. Kochukhov et al 2014), but much more demanding for late-type stars when imaging both the surface magnetic field and temperature (or brightness). Furthermore, none of the stars in this study showed any strong bumps in the Stokes I, reducing the error of the approximation.…”
Section: Zeeman-doppler Imagingmentioning
confidence: 99%
“…For this purpose we applied the ZeemanDoppler imaging (ZDI) technique using Stokes IV spectropolarimetry with a code developed by O. Kochukhov (Kochukhov et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…P lm ≡ P lm (cos θ) is the associated Legendre polynomial of degree l and order m. α lm , β lm , γ lm are the coefficients that provide the best fit to the spectropolarimetric data and are such that Equations (1) to (3) Kochukhov et al 2014) define Y lm (θ, ϕ) = c lm P lm (cos θ)e imϕ , where c lm is a normalisation constant…”
Section: The Mathematical Description Used By Zdimentioning
confidence: 99%